(untitled) (Socio-economic relations in the digital society, 2019)
Ecological paradigm, which are directed for on forming of skills and the tolerant, economy handling with natural objects, is instrumental in forming of ecological competence of potential specialist, which in the future can be professionally engaged with the problems of national economy, deciding the tasks of rational use of nature. By a resulting vector and logical result marked there is principle of socially responsibility of future specialist. Ecological paradigm of upbringing and culture of citizens determines not only the anthropological essence of society, but also the socio-economic wellbeing and health of the nation.